Sexual dimorphism of the lateral angle of the internal auditory canal and its potential for sex estimation of burned human skeletal remains - Gonçalves, David (2015)
The potential of the petrous bone for sex estimation has been recurrently investigated in the past because it is very resilient and therefore tends to preserve rather well. The sexual dimorphism of the lateral angle of the internal auditory canal was investigated in two samples of cremated Portuguese individuals in order to assess its usefulness for sex estimation in burned remains. These comprised the cremated petrous bones from fleshed cadavers (N = 54) and from dry and disarticulated bones (N = 36). Although differences between males and females were more patent in the sample of skeletons, none presented a very significant sexual dimorphism, thus precluding any attempt of sex estimation. This may have been the result of a difficult application of the method and of a differential impact of heat-induced warping which is known to be less frequent in cremains from dry skeletons. Results suggest that the lateral angle method cannot be applied to burned human skeletal remains